Qirâ’ât Dalam Perspektif Ignaz Goldziher (Studi Kritik Terhadap Pemikiran Orientalis) - Aris Hilmi Hulaimi (Universitas Darussalam Gontor, 2016)
The authenticity of Qur'an is maintained by transmission isnad from generation to generation continuously, the authenticity of Qur’an is preserued. Hence, there’re additional commentary written by the Sahabah or Companions of the Prophet. However, their additional commentaries do not decrease the authenticity of Qur’an in any way, because the text or the writing refers to qirâ’ah, and not to the contrary of the Qur’an. According to Ignaz Goldziher, he said that all problematic discourses about qirâ’ah such as ahrûf al-sab’ah, qirâ’ah al-sab’ah, and qirâ’ah syadzah, impact on the various ways of reading or different qirâ’ah implemanted. Thus becoming his reason to question the authenticity of Qur’an. A scientific research is needed to show that Qur’an is absolutely affirmed and beyond in regards to it’s authenticity as a response toward Ignaz Goldziher’s claim.